MORPHO-PHYSIOLOGICAL AND BIOCHEMICAL TRAIT BASED SELECTION OF WHEAT GENOTYPES FOR DROUGHT TOLERANCE (Bangladesh Journal of Plant Breeding and Genetics, 2015)
Drought stress is now become the most important abiotic stress for wheat in Bangladesh. Rabi season often compromised wheat production by imposing drought stress. Therefore, it has been a priority to develop drought tolerant wheat variety for Bangladesh. However, the lack of genetic variability for drought tolerance in wheat has been a major bottleneck for developing drought tolerance wheat variety. The present investigation was carried out in an aim to evaluate several exotic and locally cultivated wheat genotypes for drought tolerance based on morpho-physiological and biochemical traits. Experiment was carried out at the net house of Field Laboratory of Department of Genetics and Plant Breeding, Bangladesh Agricultural University, Mymensingh with seven replications in a RCBD design. Ten locally cultivated and exotic wheat genotypes were grown under control (100% field capacity) and drought (30% field capacity) conditions. Genotypes used in the study were identified with different types of drought tolerance mechanisms, viz., Berkut for earliness, Shatabdi for grain weight, BARI Gom 26 for spike and grain number, along with Vorobey, Berkut for enhanced biosynthesis of proline, Sokoll for undamaged leaf Chlorophyll content and relative water content, Sakha8, Gaurav, Sonalika and Shatabdi for membrane thermostability; Sakha8 and Sourav for improved stress tolerance index. The genotypes screened out with different traits related to drought tolerance can be utilized as gene source for future breeding programs.